FACTOR AFFECTING CAREER GROWTH OF FEMALE EMPLOYEES IN BANKING SECTOR - Ms. Reena Kumari Singh, Dr. Manisha (International Journal of Advanced Science and Technology, 2020)
The number of female employees has increased phenomenally in all professional sectors in past few years and women are more concerned with diversity, both positively and negatively. Women are considered as minority at workplace which puts a challenge forward to women in terms of their career progression. This study is thus aimed to study the factors which prevent women executives to grow in banking sector. The study is carried out based on 200 respondents from female employee of banks located in Delhi NCT region. The six factors that prevent the women from moving high in their career were identified using factor analysis method in the study based on responses received from working women. These six factors were work life imbalance, Non-supportive nature of colleagues, lesser opportunities to grow for women, recruitment policy, male favoritism for higher position and cultural issues.